2012
DOI: 10.1088/1367-2630/14/1/013063
|View full text |Cite
|
Sign up to set email alerts
|

Quantum equilibration in finite time

Abstract: It has recently been shown that small quantum subsystems generically equilibrate, in the sense that they spend most of the time close to a fixed equilibrium state. This relies on just two assumptions: that the state is spread over many different energies, and that the Hamiltonian has nondegenerate energy gaps. Given the same assumptions, it has also been shown that closed systems equilibrate with respect to realistic measurements. We extend these results in two important ways. Firstly, we prove equilibration o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
439
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(453 citation statements)
references
References 17 publications
13
439
1
Order By: Relevance
“…We can then talk about equilibration in a probabilistic sense. The rate of decay of these fluctuations with system size depends on the system investigated [36][37][38][39][40][41][42][43]. The important fact for us here is that for the models we study the temporal fluctuations are indeed small and should vanish for very large systems [36].…”
Section: Thermalization After a Quenchmentioning
confidence: 90%
“…We can then talk about equilibration in a probabilistic sense. The rate of decay of these fluctuations with system size depends on the system investigated [36][37][38][39][40][41][42][43]. The important fact for us here is that for the models we study the temporal fluctuations are indeed small and should vanish for very large systems [36].…”
Section: Thermalization After a Quenchmentioning
confidence: 90%
“…Usually a statement about the relaxation is proved for "sufficiently long (but finite) time", but no concrete estimates are made of how long the "finite time" will be. Although there is an interesting attempt [14] to deal with the time-scale, we find their main result not very useful for large systems [15]. If it happens that the required time is as long as, say, the age of the universe, the statement about the approach to equilibrium may not be physically relevant.…”
mentioning
confidence: 98%
“…Modern researches has revealed that even a pure quantum state, described by a single wave function without any genuine thermal fluctuation, can relax to macroscopic thermal equilibrium by a reversible unitary evolution [1][2][3][4][5][6][7][8][9][10][11]. Thermalization of isolated quantum systems, which is relevant to the zeroth law of thermodynamics, is now a very active area of researches in theory [1][2][3][4][5][6], numerics [10][11][12][13][14][15][16], and experiments [17][18][19][20][21][22][23]. Especially, the concepts of typicality [9,[24][25][26] and the eigenstate thermalization hypothesis (ETH) [10][11][12][27][28][29][30][31][32][33][34][35]…”
mentioning
confidence: 99%